Leonardo da Vinci giant of the renaissance - Barnes, John.; Encyclopedia Britannica Educational Corporation (Chicago, Ill. The Corp., 1957)
Presents the life and work of Leonardo da Vince who best exemplified the spirit of the Renaissance.
VHS.
Keywords: Leonardo da Vinci -- 1452-1519.; Art -- Technique; Composition (Art).; Painting -- Technique